The Impact of Using the STEM Education Approach with Blended Learning to Increase Students' Learning Interest - Suji Ardianti; Fahmi Yahya; Syarif Fitrianto (Indonesian Publication Center, 2020)
The current education system focuses on 21st-century learning. 21st-century learning is a system of educational renewal movements, especially in the fields of science, mathematics and technology. Educators believe that using learning that integrates technology has the opportunity to increase student interest in education. The hope, the system can be implemented in student learning processes for areas that are categorized as advanced, developing or lagging. This research was conducted at one school in Sumbawa District, West Nusa Tenggara. This research explores the impact of blended learning by using the STEM education approach to increase student interest in physics in high school. This research is qualitative research with a pretest-posttest control group design. The experimental group was taught with blended learning using the STEM education approach. The control group was prepared with conventional learning. The covariate in this study was initial knowledge. The dependent variable is learning interest which is measured using the ARCS model questionnaire. The statistical analysis used was Anacova, with a margin of error of 0.05. This research found that blended learning with STEM education approach is better in terms of increasing student interest in learning than conventional learning. The contribution in this research lies in the unique framework that is in the process of providing knowledge using blended learning integrated STEM education approaches for high school physics lessons.